Analyzing Relationship between Social Media Experience and Travel Decisions: Study on the millennials of National Capital Region - Narendra Kumar, Dr. Swati Sharma,Dr. Gaurav Kumar Gupta (International Journal of Advanced Science and Technology, 2020)
With a deep penetration of social media in everyone’s life today, it seems impossible not to include social media in consumer decision making. Be it any decision related to our purchases offline or online, social media influences our thought process and directly or indirectly remains present in the buying decisions. At the same time, with more businesses going from offline to online mode, the life of individuals have changed, particularly the use of social networking sites has revolutionized the process of information searching and sharing not only by the common man but also by the Millennials to a great extent. The present study identifies the relationship between social media and decision making process of millennials when they decide their travel plans. Major social media platforms like Facebook, Snap chat and Instagram not only attract users because of the features of editing their content but also with the features where they can share their experiences and group with the like-minded people around them. For the present study, consumer style inventory (CSI) developed by Sproles and Kendall in 1986 was used for which a quantitative study was carried out using self-administered questionnaire which was distributed among the members of millennials and involved 366 valid responses collected during October 2018 to December 2018 on 47 variables. Out of those 47 variables 36 variables were scale variables and remaining 11 variables were categorical variables. Significant differences, relationships and multivariate associations between the variables were analyzed with the help of SPSS 23.0. Validity and reliability of modified CSI scale was confirmed and exploratory factor analysis was performed. Findings of the study have been discussed at the end of the study.